Decreased Strenght Muscle Gastrocnemius of Balance Disorder in the Elderly - Dzikra Nurseptiani; Lia Dwi Prafitri; Gita Anjali (Prosiding University Research Colloquium, 2022)
Current world data is estimated that there are 500 million people with an average age of 60 years and by 2025 this data will increase to 1.2 billion. The elderly have many declines in body physiology, especially those that affect balance control such as decreased muscle strength, and changes in body posture. The Gastrocnemius muscle belongs to the leg flexor muscle group which functions for flexion of the phalanges of the foot and plantar flexion of the ankle as well as the large muscles that support the body to maintain balance. Data processing used a qualitative descriptive approach. The data obtained in the form of primary data, namely age, gender and occupation by using questionnaires and direct interviews. Furthermore, the gastrocnemius muscle strength data was assisted using a manual muscle testing (MMT) measuring instrument and the identification of the risk of falling using a time up go to test (TUGT) measuring instrument. The conclusion is that the neuromuscular changes that occur in the elderly in the form of decreased muscle mass and atrophy of the leg muscles assisted by the nervous system when working to contract will result in decreased strength in the gastrocnemius muscle. As well as changes in somatosensory function in the form of proprioceptive disorders, will have a bad effect on the balance of the elderly. This happens because muscle strength and sensory systems are included in the components of balance. Poor balance typing can put you at risk of falling. This incident proves that the strength of the leg muscles, namely the gastrocnemius muscle, is associated with the risk of falling in the elderly